2015
DOI: 10.3390/ijgi4031366
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Completeness of, and the Updates to, OpenStreetMap Data in a Heterogeneous Area in Brazil

Abstract: Abstract:The integration of user-generated content made in a collaborative environment is being increasingly considered a valuable input to reference maps, even from official map agencies such as USGS and Ordnance Survey. In Brazil, decades of lack of investment has resulted in a topographic map coverage that is both outdated and unequally distributed throughout the territory. This paper aims to analyze the spatial distribution of updates of OpenStreetMap in rural and urban areas in the country to understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 31 publications
1
41
0
14
Order By: Relevance
“…In this paper, we contribute towards this issue by focusing primarily on the coverage offered by VGI platforms in Kenya. By contributing this first case study of its type in the African continent, we augment the very limited literature [16,46] on this topic and help advance our understanding of the value of citizen-contributed data for developing countries, as well as of the challenges associated with this evolving paradigm of geospatial data collection for such communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we contribute towards this issue by focusing primarily on the coverage offered by VGI platforms in Kenya. By contributing this first case study of its type in the African continent, we augment the very limited literature [16,46] on this topic and help advance our understanding of the value of citizen-contributed data for developing countries, as well as of the challenges associated with this evolving paradigm of geospatial data collection for such communities.…”
Section: Discussionmentioning
confidence: 99%
“…However, besides the work of Haklay [46] in Haiti and Camboim et al [16] in Brazil, to the authors' knowledge, no other studies currently exist for comparing such data for developing countries. In Haklay [46], this preliminary study used the same method as in Haklay [43] to calculate road completeness, comparing the road coverage between OSM and Map Maker data obtained after the 2010 Haitian earthquake.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, very few studies have reported on the fitness-of-use of the dataset in developing countries [56,[90][91][92][93] using established quality indicators. The established methods are unsuitable to assess OSM data quality in the case of the non-availability of authoritative data [14].…”
Section: Semantic Accuracymentioning
confidence: 99%
“…An example of such dataset is one based on old but accurate cadastral data, in which newer buildings have been supplemented with other acquisition techniques such as footprints digitized from aerial images. Such approaches may result in data of variable accuracy and differing LODs, a phenomenon inherent to volunteered geoinformation (Camboim, Bravo, & Sluter, 2015;Fan, Zipf, Fu, & Neis, 2014;Senaratne, Mobasheri, Ali, Capineri, & Haklay, 2017;Touya & Brando-Escobar, 2013;Uden & Zipf, 2013). Because such data are becoming increasingly used for spatial analyses (Wendel, Murshed, Sriramulu, & Nichersu, 2016), it is worthwhile to investigate for which portions of the dataset caution should be exercised due to lower reliability than in other parts of the dataset.…”
Section: Introductionmentioning
confidence: 99%